Wednesday

April 23, 2014

April 23, 2014

Posted by **mic** on Saturday, August 28, 2010 at 10:32pm.

3x-2(y+2)=-6

4(x+1)-y=7

- geometry -
**Jen**, Saturday, August 28, 2010 at 11:09pm3x-2y-4=-6

3x-2y=-2*

4x+4-y=7

4x-y=3*

So your 2 new equations are

3x-2y=-2

4x-y=3

Multiply the bottom equation by -2 to cancel the y's gives us

-8x+2y=-6

3x-2y=-2

-5x=-4

x=4/5

Plug the x value into either of your "2 new equations above" to figure out y.

**Related Questions**

geometry - The measures of the angles in a quadrilateral are represented by x, ...

algebra - Solve the system by graphing. 3x+y=6 3x-y=0 I'm kind of unsure about ...

MATH PLEASEEEEE - I have a question, if f(x)=x/2 and g(x)=3x+1 find: a) (f+g)(x...

Geometry - Solve for x. x(x+3)=2^2 I think I'm doing this all wrong. Here is the...

Geometry - Solve for x. x(x+3)=2^2 I think I'm doing this all wrong. Here is the...

Geometry - How do I solve this problem? Point P is between points L and M. LM = ...

GEOMETRY - How to solve for x in geometry ? for example - there is a line ...

algebra - solve 4^3x-4=32^x+2 Please help! Do you mean 4^(3x) -4 = 32^x +2 ? yes...

geometry - how do I solve m<1=3x+11

geometry - 3x + y + 7 + 90 = 180 deg. how to solve?